Discourses on Violence in Costa Rica, El Salvador, and Nicaragua: Laws and the Construction of Drug- and Gender-Related Violence - Peter Peetz
In Central America, legislation aiming to reduce violence and crime has become an important topic in the security debate. Focusing on Costa Rica, El Salvador, and Nicaragua, this paper analyzes laws and other legal texts regarding the trade in and consumption of drugs on the one hand, and gender-related violence on the other. It shows how the content and the wording of legal texts contribute to the social construction of stereotyped offenders, such as youth gang members, drug users, or foreign nationals. The legal texts in Costa Rica, El Salvador, and Nicaragua reflect both the hegemonic and the counter-discursive influences on each country’s legal discourse.Central America, violence, drugs, gender, legal discourse